(untitled) (Proceedings of the International Scientific Conference "Social Changes in the Global World", 2019)
The beginning of the new millennium is recognizable by the fact that the states, especially from the European continent, endeavor to adapt to the imposed problems associated with mass migrations. Economic poverty, wars and forced migration encourage the migration process, and cities, especially megalopolises, are their final destination. The war in Syria and the global economic crisis in 2015 spurred the European migrant crisis. In this context, the EU has failed to fully find the right solution for their distribution and integration in the new environment. We should seek for the answer in the models of multiculturalism, interculturalism and cosmopolitanism. The enormous influx of immigrants represents a threat of changing socio-cultural identities primarily to the western developed societies, where xenophobic outbursts are more frequent. Changes in the demographic composition caused by migration are most intensely felt in the urban area. In this context, each state is guided by political decisions within national interests, which often encounter difficulties by the international public. Without doubt, migration policy, as well as media coverage, contribute to this plan. Any major migration causes a cultural shock in the domicile population. The increase of the population in the city, especially when it significantly exceeds the capacities, brings with it problems in the urban area, the labor market, ecology and its pollution.